The similarities in the Holy Qur’an, a detailed analytical and applied study - Bouhalima, Ziad Omar Hamad Mahmoud (Al-Mukhtar Journal of Social Sciences, 2026)
The Noble Quran is still a vast ocean of knowledge, encompassing various sciences. Among its sciences are the precise and ambiguous verses, and this study focuses on the ambiguous verses because they are the ones that differ in interpretations, leading to questions such as: Are the ambiguous verses part of what Allah has exclusively reserved knowledge of? Or are they open to the general public to explore? Or are they specifically for the scholars? Or are they only for those deeply rooted in knowledge? And is it permissible to delve into them? And what is the ruling for those who approach them without knowledge? In this study, I have presented various opinions and weighed what is correct, by the will of Allah, after defining ambiguity in language and terminology. I have also highlighted the different types of ambiguity and provided examples from the Noble Quran. By examining the introduction and conclusion, the overall subject becomes clear. I have titled my humble research: "An Analytical, Detailed, and Applicative Study of Ambiguity in the Noble Quran." In this research, I have included different opinions, and to the best of my ability, I have clarified and explained the subject matter.